EFFICACY OF DIFFERENT CONCENTRATION OF PHYSIOLOGICAL SALINE SOLUTION ON THE REPRODUCTIVE PERFORMANCE OF Clarias gariepinus (BURCHELL, 1822) - Abubakar, A, A.; Miga, I. H.; Haruna, M. Y.; Dachi, W.M.; Aliyu, M. D.; Abdulkarim, M (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The effect of different dilution factor of physiological saline solution in milt and its influence on reproductive performance of Clarias gariepinus were investigated. 2500g each of male and female C. gariepinus were collected from the teaching and research farm of the department fisheries and aquaculture, Federal University Dutse Jigawa. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments, each replicated three times. The physiological saline concentration of each treatment was T1=0.3%, T2=0.5%, T3=0.7% and T4=0.9%. Data on egg fertilization, hatching, and survival rates were collected. The result shows that fertilization rates were higher (82.08±9.37) in T2 (0.5g/1000ml), while hatching rates were better in T2 and T1 at 82.97±16.71 and 75.04±5.26 respectively, the values were not significantly different (p>0.05). There was a higher significant difference (p<0.05) in survival rate for T1 (85.48±19.53) than other treatments. The saline concentration dilution for optimum fertilization, hatchability and survival rate ranged from 0.3% to 0.5%. Higher saline concentrations negatively impact fertilization and survival rates in African catfish breeding. Optimal breeding outcomes may also depend on other water parameters and brooder fish health.